Estudio del relave minero de la planta de beneficio santa lucía código 191038 del sector la maravilla de la parroquia pucará, cantón pucará, provincia del Azuay, con fines de utilización en morteros de pega de unidades de mampostería. - Sánchez Valverde, Yohana Estefanía (2019)
Mining activity in Ecuador generates lots of waste during the exploding and beneficial of minerals, which are accumulated in big areas or have been put into nearby hydric bodies causing environmental passives. The reuse of these sub products in the building industry saves resources and energy, as well as reducing environmental problems related with their final disposal; although tailings are the most abundant industrial sub products, only a few studies have been carried out in order to assess its potential reuse. This study presents an experimental design that uses physical, geochemical and mineralogical tests in order to assess the use of tailing at “Santa Lucia” treatment and beneficial plant, as a fine aggregate to mortars of masonry. In general, it was observed that the mortar’s properties were related to fluidity ranging from 100 to 120 % according to the hexagon N° 1 points from 4 to 10, and also to the points on hexagon N° 2 from 13 to 20. Compression resistance showed type S mortars with values from 12.7 to 15.8 MPa using tailing percentages of 10, 15, 20, 25, and 50; but with different variations of liquid-cement; it should be noted that the 50 % sample was more expensive than the others. The best results were found with l-c mixtures of 0,6 through 0,65. The adherence test of four specific samples determined that through the use of tailing 100 % maintain the adherence with masonry.